PROBLEMS ON THE ABUSE OF DOMINANT POWER OF THE DIGITAL PLATFORM SERVICE PROVIDERS - Leelabooranasak, Roongrot (Journal of MCU Nakhondhat, 2024)
This research aims 1) To study and understand the digital platform business, including the business model of digital platform services and the market dominance of the digital platform service sector; 2) To examine and understand the approaches and measures for preventing the abuse of dominant power by digital platform service businesses in Thailand and other countries; and 3) To explore ways to amend and improve Thailand's current Trade Competition Law or to enforce new laws to effectively prevent and regulate the digital platform service business in a manner that is appropriate and fair within the context of Thai law. This includes a comparative study between the Trade Competition Act B.E. 2560 (2017) and relevant rules and regulation, with foreign laws and legal measures from the European Union, Germany, and China. This research is qualitative in nature, employing documentary research methodology which involved examining data from secondary data sources from 4 Thai literature sources and 7 foreign literature sources. This research found that the current consideration of the abuse of dominant power in the digital platform service business under Thailand's Trade Competition Law is insufficient and inappropriate due to the unique characteristics and complexity of such businesses, which differ from traditional businesses. Consequently, the application of the current law cannot adequately address emerging cases. The researcher therefore suggests amending the Trade Competition Law and introduce additional legal measures to comprehensively regulate the digital platform service business and promoting free and fair competition in the market.